Changes in the trajectory and skating speed in the curved section during the maximum effort short-track speed skating. - Okabe, F.; Kawai, T.; Yokozawa, T.; Yuda, J.; Akazawa, N.; Fujita, Z. (Japan Journal of Physical Education, Health and Sport Sciences, 2025)
This study aimed to investigate the factors related to reduction of short-track speed-skating lap time by examining the relationships between lap time, skating trajectory, skating speed, average section speed, and excess distance in a curved section during maximum effort. The study included 8 male skaters (age, 21 ± 5 yr, height, 1.67 ± 0.05 m, weight, 63.9 ± 4.7 kg), who skated for 3 laps with maximum effort. The curve section was defined as C1 for the first half up to the midpoint of the curve and C2 for the second half after the midpoint. The time taken in the first half of the second lap, skating trajectory, skating speed, change of speed, section average speed, and excess distance covered in the curved section were calculated. The skating speed was expressed as 100% for the entire curved section. The following results were obtained: